2022
DOI: 10.3390/ijerph19116484
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sports Activities on Prosocial Behavior of Children and Adolescents: A Systematic Literature Review

Abstract: Prosocial behavior plays a key role in interpersonal relationships during the growth of children and adolescents. Good prosocial behavior is the foundation for the healthy development of children and adolescents. In recent years, the role played by some sports activities in children and adolescents’ prosocial behaviors has attracted much attention. However, the effects of physical activity on prosocial behavior have not been summarized. Objective: We aimed to clarify the role of sports activities in children a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 71 publications
3
19
0
Order By: Relevance
“…All participants described a development from predominantly egoistic to more balanced behaviour. These perceived changes in behaviour through sporting activities are accordance with recent studies, where sport was observed as beneficial for social behaviour in general [ 22 , 23 , 24 ]. The participants’ former predominantly egoistic behaviour in climbing may be rooted in their tendency towards self-centred behaviour at the time when they still went to school.…”
Section: Discussionsupporting
confidence: 91%
“…All participants described a development from predominantly egoistic to more balanced behaviour. These perceived changes in behaviour through sporting activities are accordance with recent studies, where sport was observed as beneficial for social behaviour in general [ 22 , 23 , 24 ]. The participants’ former predominantly egoistic behaviour in climbing may be rooted in their tendency towards self-centred behaviour at the time when they still went to school.…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that regular and extensive training in adults is associated with changes in cardiac morphology, namely, increased left and right ventricular cavity dimension, wall thickness, and mass [ 82 , 83 , 84 ]. Cardiac adaptations to exercise also occur in children and adolescents, independent of the influence of growth and maturation [ 85 ]; a recent systematic review of echocardiographic studies concludes that these adaptations are more pronounced in structural left ventricular parameters, with the functional parameters being preserved or slightly improved by exercise [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of this research, the fact that there is no statistically significant difference in the nationality variable other than the general communication and behavioral communication subdimension can be interpreted as individuals either having similar feelings and thoughts or that the environment they are in should be diversified a little more. Just as physical activity (playable at any skill level, active recreational play and sports) improves the psychological variables of mental health and helps children and adolescents actively integrate into society, physical activity has also been shown to reduce aggressive behavior in children and adolescents (Li & Shao, 2022). Considering this aspect of sports, it is very important to evaluate the results by designing and implementing the programs well to meet the needs of disadvantageous young people (Tidmarsh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, where families are ignorant for many reasons and children need to learn that cognitive, social, emotional, communication and language levels can be improved with movement, it is recommended to implement awareness programs, courses, even adult education and projects in children, especially for adults (Orhan, 2019). In addition, children and adolescents who actively participate in physical activities have better prosocial behaviors and fewer interpersonal problems (Li & Shao, 2022). For this reason, the Ministry of Youth and Sports supports the implementation of various projects in order to contribute to the personal and social development of individuals, to advance their existing potentials and to adapt to social life, taking into account the needs of society and young people (Yavuz, 2018).…”
Section: Introductionmentioning
confidence: 99%